An Efficient Decision Making system for Sustainable Fertilization (Global Journal of Computer Science and Technology, 2023)
Farmers often face challenges in effectively managing fertilizer use and must rely on expert advice to maximize yields while minimizing fertilizer waste Precipitation plays an essential role in the loss of nutrients after each rainfall event Timely rainfall can help nutrients penetrate into the root zone of the soil and dissolve dry fertilizer thereby improving nutrient absorption However excessive rainfall increases the risk of runoff leading to the loss of key nutrients such as nitrogen N essential elements such as phosphorus P and potassium K and other nutrients such as manganese Mn and boron B Of the ground The study used time-series data on rainfall and crop fertility It uses an improved version of the random forest algorithm to predict the optimal nutritional needs of different crops The method proposed in this study aims to improve soil fertility by offering nutrient recommendations that promote ideal crop growing conditions while minimizing leaching and runoff nutrient overflow